Ruminal fermentation pattern of acidosis-induced cows fed either monensin or polyclonal antibodies preparation against several ruminal bacteria - Pacheco, Rodrigo D. L.; Souza, Johnny M.; Marino, Carolina T.; Bastos, João Paulo S. T.; Martins, Cyntia L.; Rodrigues, Paulo H. M.; Arrigoni, Mario D. B.; Millen, Danilo D. (Frontiers in Veterinary Science, 2023)
This study was designed to evaluate a spray-dried multivalent polyclonal antibody preparation (PAP) against lactate-producing bacteria as an alternative to monensin (MON) to control ruminal acidification. Holstein cows (677±98 kg) fitted with ruminal cannulas were allocated in an incomplete Latin square design with two 20 days period. Cows were randomly assigned to control (CTL), PAP, or MON treatments. For each period, cows were fed a forage diet in the first 5 days (d -5 to d -1), composed of sugarcane, urea and a mineral supplement, followed by a 74% concentrate diet for 15 days (d 0 to d 14). There were no treatment main effects (P > 0.05) on dry matter intake (DMI) and microbial protein synthesis. However, there was a large peak (P < 0.01) of intake on d 0 (18.29 kg), followed by a large decline on d 1 (3.67 kg). From d2, DMI showed an increasing pattern (8.34 kg) and stabilized around d 8 (12.96 kg). Higher mean pH was measured (P < 0.01) in cattle-fed MON (6.06 vs. PAP = 5.89 and CTL = 5.91). The ruminal NH3-N concentration of CTL-fed cows was lower (P < 0.01) compared to those fed MON or PAP. The molar concentration of acetate and lactate was not affected (P > 0.23) by treatments, but feeding MON increased (P = 0.01) propionate during the first 4 days after the challenge. Feeding MON and PAP reduced (P = 0.01) the molar proportion of butyrate. MON was effective in controlling pH and improved ruminal fermentation of acidosis-induced cows. However, PAP was not effective in controlling acidosis. The acidosis induced by the challenge was caused by the accumulation of SCFAs. Therefore, the real conditions for evaluation of this feed additive were not reached in this experiment, since this PAP was proposed to work against lactate-producing bacteria.